2019
DOI: 10.1136/vr.104974
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tear production using the Schirmer tear test I in healthy cats; effect of age, life stage, sex, breed and neuter status

Abstract: BackgroundThe purpose of this study was to evaluate the values of Schirmer tear test (STT) and determine effects of age, life stage, sex, breed and neuter status on tear production in healthy cats.MethodsThree hundred and forty-three domestic shorthair (DSH) and Persian cats, 50 days through 18 years old, were examined in this study. STT I was used to measure tear production in both eyes of each cat.ResultsA mean STT 14.9±4.8 mm/min was calculated for the eyes of all cats. There was a significant difference be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 18 publications
4
16
4
Order By: Relevance
“…This finding was in line with a previous report on dogs 23 . In cats, sex is reported to have no effect on STT, whereas neuter status has been suggested to have an impact on STT 22 …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding was in line with a previous report on dogs 23 . In cats, sex is reported to have no effect on STT, whereas neuter status has been suggested to have an impact on STT 22 …”
Section: Discussionsupporting
confidence: 93%
“…7 In cats, a brachycephalic breed (Persian) has been reported to have higher tear production compared to domestic shorthaired cats. 22 In the present study, no significant correlation was observed between STT and TBUT in dogs. This finding was in agreement with the results of a study in which no correlation was found between TBUT and STT in cats experimentally infected with FHV-1.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…First, the SST strips were placed in the ventral conjunctival sack without difficulty and all dogs tolerated the test well. The STT has long been the clinical standard for evaluating aqueous tear production [17,18] and general reference values are known in different animal species such as dogs, cats, rabbits, and horses [19][20][21][22][23][24], and presumably, these values may differ among various dog breeds [23][24][25].…”
Section: Discussionmentioning
confidence: 99%